Exchange Rate Pass-Through Investigation for Turkish Economy - Kotil, Erdoğan (Frontiers in Applied Mathematics and Statistics, 2020)
Turkish economy continued to rapidly opening up to the outside for the last 40 years. It has long been in the top 20 largest economies in the world. Exchange rate is an important variable affecting micro and macro variables in the economy. This study aims to investigate the effect of exchange rate changes on the producer and consumer prices in Turkey by using the VAR model. Results show that the degree of transition with effect-response functions and how the prices were affected by variance decomposition by using the 2005-2019 monthly data. CPI's response to the change in nominal exchange rate was found to be greater than PPI. The end of the impact is shorter than CPI’s impact.